Polyphenolic Compounds Isolated from Marine Algae Attenuate the Replication of SARS-CoV-2 in the Host Cell through a Multi-Target Approach of 3CLpro and PLpro - D. P. Nagahawatta; N. M. Liyanage; Jun-Geon Je; H. H. A. C. K. Jayawardhana; Thilina U. Jayawardena; Seong-Hun Jeong; Hyung-Jun Kwon; Cheol Soo Choi; You-Jin Jeon (Marine Drugs, 2022)
A global health concern has emerged as a response to the recent SARS-CoV-2 pandemic. The identification and inhibition of drug targets of SARS-CoV-2 is a decisive obligation of scientists. In addition to the cell entry mechanism, SARS-CoV-2 expresses a complicated replication mechanism that provides excellent drug targets. Papain-like protease (PLpro) and 3-chymotrypsin-like protease (3CLpro) play a vital role in polyprotein processing, producing functional non-structural proteins essential for viral replication and survival in the host cell. Moreover, PLpro is employed by SARS-CoV-2 for reversing host immune responses. Therefore, if some particular compound has the potential to interfere with the proteolytic activities of 3CLpro and PLpro of SARS-CoV-2, it may be effective as a treatment or prophylaxis for COVID-19, reducing viral load, and reinstating innate immune responses. Thus, the present study aims to inhibit SARS-CoV-2 through 3CLpro and PLpro using marine natural products isolated from marine algae that contain numerous beneficial biological activities. Molecular docking analysis was utilized in the present study for the initial screening of selected natural products depending on their 3CLpro and PLpro structures. Based on this approach, Ishophloroglucin A (IPA), Dieckol, Eckmaxol, and Diphlorethohydroxycarmalol (DPHC) were isolated and used to perform in vitro evaluations. IPA presented remarkable inhibitory activity against interesting drug targets. Moreover, Dieckol, Eckmaxol, and DPHC also expressed significant potential as inhibitors. Finally, the results of the present study confirm the potential of IPA, Dieckol, Eckmaxol, and DPHC as inhibitors of SARS-CoV-2. To the best of our knowledge, this is the first study that assesses the use of marine natural products as a multifactorial approach against 3CLpro and PLpro of SARS-CoV-2.